Verification of tree induced suction with numerical model - Mohd Fakhrurrazi, Ishak; M. F., Zolkepli; Mohd Yusri, Mohd Yunus; Nazri, Ali; Azman, Kassim; M. S.I., Zaini (Elsevier Ltd, 2021)
This study discusses the validation between explorations of transpiration on the unsaturated soil zone with unsaturated flow equation of tree water uptake model. Numerical simulation was performed to the model of the slope in relation to moisture migration patterns in the unsaturated zone within the vicinity of mature tree. The results of numerical simulation conducted on typical slope geometry model with tree at the toe of the slope of induced transpiration were later presented in this study. The results of numerical simulation and field monitoring of suction against depth are in acceptable condition. It is important to note that, several of the differences between simulated numerical and field measurement are related to inconsistence effect of root density.